The spatial analysis of the population settlement peculiarities of Volyn region using centrographic method - Volodymyr Lazhnik; Serhiy Pugach (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
To analyze the characteristics of population settlement of certain areas different methodological approaches and techniques are used, among which сentrographic method occupies a special place. Centrographic method allows to determine the center of population gravity, the degree of its concentration around the central points of the territory, to identify the space-time changes in their placement, to compare the centers of population areas (democenters) with the gravity centers of the other geographical phenomena, which are obtained by similar formulas.